Scalable parallel finite volume lattice Boltzmann method for thermal incompressible flows on unstructured grids - Xu, Lei; Chen, Rongliang (International journal of heat and mass transfer, 2020)
•A parallel cell-centered finite volume thermal lattice Boltzmann method for two-dimensional unstructured grids is proposed to simulate thermal incompressible flows.•The proposed algorithm scales up to 6000 processor cores with 96.50% parallel efficiency for a case with over 5 billion unstructued grid cells. A parallel cell-centered finite volume thermal lattice Boltzmann method (FV-TLBM) for two-dimensional unstructured grids is proposed to simulate thermal incompressible flows. The governing equations for the velocity and temperature fields are solved using the D2Q9 lattice model in the lattice Boltzmann method and the cell-centered finite volume method. In this paper, the advective fluxes in the governing equations are evaluated by a low-diffusion Roe scheme, and the gradients of the particle distribution functions are computed with the least-square approach. To simulate large-scale complex flows within a reasonable time, a parallel algorithm for the FV-TLBM on unstructured grids is devised. The present method is validated by numerical simulations of the natural convection in a square cavity and natural convection in a concentric annulus at different Rayleigh numbers. The results obtained by the proposed method agree well with previous studies. The parallel performance results show that the proposed algorithm has considerable scalability and the parallel efficiency is as high as 96.50% for a case with over 5 billion grid cells using 6000 processor cores.